Trigonella disperma (Fabaceae): Typification, Description and Phytogeography - Aghaahmadi, Majid; Saeidi, Hojjatollah; Assadi, Mostafa (Phytotaxa, 2018)
Based on a comprehensive study of freshly collected material, type and herbarium specimens Trigonella disperma is here typified and a full description, illustrations of the fruit and floral parts, a distribution map and taxonomic remarks provided for this species.